2023
DOI: 10.3390/su151612202
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Physical and Chemical Characteristics of Dust in Open Pit Coal Mine Crushing Stations and Closed Dust Reduction Methods

Abstract: As an important link in open-pit mining production, the crushing station produces a large amount of dust during the production process. Dust has the characteristics of a wide spread area, great harm, and difficult governance. Therefore, dust control has become a key issue that needs to be solved in open-pit mining. In this article, we assess results after high-speed cameras and dust concentration detectors are installed around the crushing station to monitor the dust concentration in the surrounding air. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The dependence of the compressive strength of concrete (R C ) on CD content (%) presented in Figure 10 is described by a polynomial of the fourth degree R C == 39.11 + 0.84 x + 0.0727 x 2 − 0.0545 x 3 + 0.00325 x 4 , R 2 = 0.968 (7) According to the results of determining the compressive strength, presented in Figure 10, it was found that when replacing part of the cement with CD in the amounts of 2% and 4%, small increases in strength are observed up to 2.8% and 6.6%, respectively. However, with a further increase in the amount of CD, a negative effect is observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence of the compressive strength of concrete (R C ) on CD content (%) presented in Figure 10 is described by a polynomial of the fourth degree R C == 39.11 + 0.84 x + 0.0727 x 2 − 0.0545 x 3 + 0.00325 x 4 , R 2 = 0.968 (7) According to the results of determining the compressive strength, presented in Figure 10, it was found that when replacing part of the cement with CD in the amounts of 2% and 4%, small increases in strength are observed up to 2.8% and 6.6%, respectively. However, with a further increase in the amount of CD, a negative effect is observed.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, in many countries of the world, there is a big problem associated with the accumulation of waste from the mining and processing industries [1][2][3][4][5], in particular, for industrial mining purposes. For example, in coal mines and related industries, a huge amount of by-material of coal products is formed that is not used for its intended purpose [6,7]. One of the most typical representatives of this waste group is coal dust.…”
Section: Introductionmentioning
confidence: 99%